'Bodies that splutter' – theorizing jouissance in bareback and chemsex porn. Issue 1 (2nd January 2019) - Longstaff, Gareth
ABSTRACT: This article explores associations between the psychoanalytic theory of jouissance and representations of bareback and chemsex between cis-gendered men in gay porn. It uses the concept of 'bodies that splutter' to focus on how tensions allied to the definition and interpretation of jouissance can be used as a foundation to interpret and reposition a queer and psychoanalytic politics of bareback and chemsex as porn. In so doing, the article will suggest that pornographic practices of bareback and chemsex in the output of UK director Liam Cole and US website RawFuckClub.com attempt to frame these practices of gay male desire as phallic jouissance. Working with the notion of 'bodies that splutter', the article will transpose Judith Butler's concept of performative bodies that matter and Tim Deans' unconscious bodies that mutter to consider a dialogue between pornography and jouissance where bodies also 'splutter'.